Avaliação comparativa da atividade antinociceptiva de enantiômeros de citronelal: uma abordagem in silico e in vivo - Costa, Aratã Oliveira Cortez (2023)
Due to the complexity of pain, encompassing physical, cognitive, psychological, and behavioral aspects, the management of pain involves various approaches, especially in developing countries, where the search for new treatment options for emerging or debilitating diseases is significant; the use of medicinal plants is a relevant practice. Recent studies have focused on the activity of monoterpenes on nociception-related receptors, and the identification of specific interactions of monoterpenes promises to pave the way for the development of new therapeutic strategies in pain control. In this context, the present study aimed to comparatively evaluate the effects of the monoterpene citronellal, distinguishing its activities for the isomers (R)-(+) and (S)-(-) citronellal and determining the possible mechanism of action by which this activity is performed. As an initial study, a computational molecular docking analysis was performed, where the compounds (R)-Citronellal and (S)-Citronellal showed affinity for glutamatergic receptors and TRPA1 receptors, indicating their potential as active agents in these pathways and opening the way for in vivo studies. Methodologies related to the study of motor coordination (Rotarod), as well as the evaluation of nociception in physical (Hot plate) and chemical (Formalin, glutamate, and capsaicin) parameters, were used to confirm their activity and possible detection of the mechanism of action. Both isomers did not demonstrate significant effects on the motor coordination of the tested animals. The isomer (S)-(-) citronellal showed better results compared to its structural homologue, exhibiting antinociceptive effects in the formalin and hot plate tests, even at a lower concentration (100 mg/kg), and with fewer side effects. However, the study did not fully elucidate the mechanism of action of this isomer, as its activity was not reversed with the use of antagonists for nociception-related pathways. On the other hand, the isomer (R)-(+) citronellal demonstrated activity only at a concentration of 150 mg/kg and had its mechanism of action related to the opioid pathway, a pathway already correlated with nociception control treatments, although also associated with unwanted side effects. This underscores the importance of future research to elucidate the molecular mechanisms involved in pain modulation and the development of more effective therapeutic strategies for pain management. Therefore, monoterpenes show promise as agonists or potential modulators of pain control receptors.